Financial Management Analysis for the Development of SMEs in the Era of the Industrial Revolution 4.0 (Case Study on SMEs in Junrejo City, Batu) - Septiana Epliani Marni; Poppy Indrihastuti; Nur Ida Iriani; Moch Nurhidayat (International Journal of Management and Business, 2026)
Technological developments in the Industry 4.0 era present digital business models, artificial intelligence, and big data that drive changes in SME financial management. This research aims to analyze the financial management of SMEs in the era of the Industrial Revolution 4.0. Using a qualitative approach with a descriptive design, the study was conducted in Junrejo District, Batu City, from December 2024 to January 2025. Primary data is obtained through observation and interviews with SME owners, while secondary data comes from business documents and academic references. The sample was determined by purposive sampling, including SMEs operating for at least five years and applying technology in production, promotion, and finance. Data analysis was carried out thematically through reduction, presentation, and conclusion. The study results show that using technology in financial recording and business operations increases the efficiency and competitiveness of SMEs. A study on three SMEs, namely Tohu Srijaya and Orchid Nursery, shows the use of accounting, IoT, and e-commerce software in managing cash flow, investment, and access to financing. Good financial literacy allows for more optimal financial management. Therefore, increased financial understanding, technology adoption, and government support in access to funding and training are needed for SMEs to develop sustainably.